(untitled) (ACUMEN: INTERNATIONAL JOURNAL OF MULTIDISCIPLINARY RESEARCH, 2026)
The article analyzes the current state of mobile services in the libraries of Uzbekistan. Existing mobile library and near-library applications are examined as two major groups: open nationwide platforms and specialized educational services with restricted access. Using the examples of Mutolaa, Kitob.uz, Asaxiy Books, KUAF Mutolaa, SamDTU Books, and TDIUSF Kutubxonasi, the study compares content type, target audience, access model, language policy, and functional capabilities.